Characterization of a Novel α-Neoagarobiose Hydrolase Capable of Preparation of Medium- and Long-Chain Agarooligosaccharides - Jiang, Chengcheng; Liu, Zhen; Sun, Jianan; Mao, Xiangzhao (Frontiers in Bioengineering and Biotechnology, 2020)
α-Neoagarobiose hydrolase plays an important role in saccharification processes of marine biomass. In this study, a α-neoagarobiose hydrolase from Streptomyces coelicolor A3(2), designated as ScJC117, was identified, purified and characterized. It has a sequence of 370 amino acids and belongs to the GH117 family. ScJC117 exhibited good activity under optimal hydrolysis conditions of pH 6.0 and 30°C, where it showed the Km and kcat for neoagarobiose of 11.57 mM and 0.48 s-1, respectively. ScJC117 showed the ability to hydrolyze neoagarooligosaccharides with the polymerization degrees of 2-14. Basis of catalytic activity toward the first α-1,3-glycosidic bond of the neoagarooligosaccharides from the non-reducing end, ScJC117 can be classified as an exo-type α-neoagarobiose hydrolase. These results suggested that ScJC117 could be used in the preparation of odd agarooligosaccharides (especially agaroheptaose-agaroundecaose) and 3, 6-anhydro-L-galactose, which has as functional food additive potential. Moreover, ScJC117 can be used for comprehensive utilization of red algae.